Screening of Psychological Distress in Cancer Patients During Chemotherapy: A Cross-sectional Study - Singh, Raja Paramjeet Banipal (Indian J Palliat Care, 2015)
OBJECTIVE: The objective of this prospective, noninterventional, 8-months, observational study was to analyze and compare depression, anxiety, and stress (DAS) levels and their impacting factors in homogenous surviving cancer patients receiving chemotherapy as compared to normal control. MATERIALS AND METHODS: A prospective and descriptive study was carried out jointly by Pharmacology and Oncology departments of a tertiary care center in Malwa region of Punjab. The data was collected by administering the validated questionnaire/response (21-item Depression Anxiety and Stress Scale (DASS-21)) after taking ethical approval and informed consent. RESULTS: All eligible 300 subjects participated in the study and they were compared with 300 matched control. The mean age of the cases (cancer patients) and controls was 50.58 ± 13.64 and 46.1 ± 11.78 (mean (M) ± standard deviation (SD)) years. Statistical significant difference was observed in mean ‘scoring of DAS’ in cancer patients when compared with control groups. Anxiety mean scoring showed a statistical significant difference in groups (according to chemotherapy cycles given and duration of disease). Stress was more observed in breast cancer patients. CONCLUSION: Holistic approach in cancer management including psychological evaluation and its solution at appropriate time/stage signifies the need of time as the present study revealed that the percentage of DAS as per the DASS scale was 90, 56, and 28%, respectively. A judicious diagnosis with an apposite intercession including psychological consultation with social support at appropriate time may alleviate the extra burden of psychological disorder, rather enhance the quality of life of cancer-affected rural population.